The Historiography of Medieval Monasticism: Perspectives from Northern Europe - Emilia Jamroziak (Religions, 2021)
The article provides a thematized discussion of the development of the historiography of European monasticism in northern Europe (north Atlantic, North Sea to the Baltic). Whilst it does not offer a comprehensive overview of the field, it discusses the significance of major currents and models for the development of monastic history to the present day. From focusing on the heritage of history writing “from within”—produced by the members of religious communities in past and modern contexts—it examines key features of the historiography of the history of orders and monastic history paradigms in the context of national and confessional frameworks. The final section of the article provides an overview of the processes or musealization of monastic heritage and the significance of monastic material culture in historical interpretations, both academic and popular.